Perlindungan Hukum Bagi Pemilik Tanah yang Tumpang Tindih (Overlapping) Kepemilikan (Studi Putusan Mahkamah Agung Nomor 221 PK/PDT/2014) - Luvianti, Teressyavira; Rasji, Rasji (Universitas Ekasakti, 2023)
Legal protection for land owners in Indonesia in resolving overlapping ownership conflicts highlights the complexity and challenges in the legal system. With UUPA as the basic framework, the analysis involves evaluating successes and weaknesses in aspects of land registration, dispute resolution mechanisms, and recognition of customary rights. High costs and slow land registration processes are obstacles, but efforts to speed things up and provide transparency have been made. Dispute resolution mechanisms, such as mediation, show progress, but challenges related to bureaucracy and accessibility remain. Recognition of customary rights needs to be strengthened to reduce gaps with positive law. Despite awareness of improvements, law enforcement remains slow, posing a risk of land ownership rights being violated. To improve protection, reforms are needed in the costs and efficiency of land registration, strengthening dispute resolution mechanisms, further recognition of customary rights, and serious improvements in law enforcement. A balance between regulation, community participation and law enforcement is key to achieving effective legal protection for land owners, supporting sustainability and inclusiveness in development in Indonesia.